2009
DOI: 10.1111/j.1365-2648.2009.04995.x
|View full text |Cite
|
Sign up to set email alerts
|

The Internet as a research site: establishment of a web‐based longitudinal study of the nursing and midwifery workforce in three countries

Abstract: Many of the issues reported in this paper are transitional in nature at a time of rapid technological development. The development of on-line methods and tools is a major and exciting development in the world of research. Research via the world-wide web can support international collaborations across borders and cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 24 publications
(27 reference statements)
0
60
0
Order By: Relevance
“…Details of the NMeS have been reported elsewhere. [18][19][20] Briefly, the DeC Study aimed to be a 5-year cohort study using a purpose-built internet-based survey (see http://doctors.e-cohort. net).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the NMeS have been reported elsewhere. [18][19][20] Briefly, the DeC Study aimed to be a 5-year cohort study using a purpose-built internet-based survey (see http://doctors.e-cohort. net).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…All participants had a unique ID generated automatically at registration. [18][19][20] Data processing and statistical analysis Data were copied from the SQL database into SAS ® software, Version 9.2 (SAS Institute Inc., Cary, NC, USA) where data cleaning was undertaken. Participants were not personally identified in analysis datasets; all datasets included the participant ID only.…”
Section: Data Storage and Securitymentioning
confidence: 99%
“…Twenty-one percent of American Psychological Association journals have published at least one article that reported on Internet research, with 39% being correlational studies and 25% having a college student sample (Skitka & Sargis, 2006). Some advantages to using the Internet for research include the time saved in collecting data, avoidance of waste and costs associated with paper instruments, easy to download data for analysis, and access to underrepresented samples (Fan & Yan, 2010;Huntington et al, 2009;Skitka & Sargis, 2006). Even though the Internet facilitates access to underrepresented samples, there is conflicting evidence for whether or not it gives researchers a diverse sample.…”
Section: Methodsmentioning
confidence: 99%
“…The web design can also be a limitation in that participants may end the survey early by misinterpreting the progress bar indicating completion of a section versus the survey. Modes of delivering the survey and reminding participants to complete the survey (e.g., spam-blocking features on the computer) may prevent the participant from receiving the web link for the survey (Fan & Yan, 2010;Huntington et al, 2009;Skitka & Sargis, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The NMeS is a longitudinal web-based study of 7,604 nurses and midwives in three countries: Australia, New Zealand and the United Kingdom. The full detail of the NMeS is described in Turner et al [21] and Huntington et al [22] and the profile of the cohort has been reported. Internet-based surveys raise important technical and methodological issues which need to be carefully considered before widespread implementation [10,13,20] .…”
Section: Instrument Developmentmentioning
confidence: 99%